Uncertainty quantification in prediction of material properties during additive manufacturing. (1st July 2017) - Hu, Zhen; Mahadevan, Sankaran
Abstract: Based on our experience gained from uncertainty quantification (UQ) of traditional manufacturing, this paper discusses UQ for additive manufacturing with a focus on the prediction of material properties. Applications of UQ methods in traditional manufacturing are briefly summarized first. Based on that, we investigate how the state of the art UQ techniques can be applied to AM process to quantify the uncertainty in the material properties due to various sources of uncertainty. The UQ of ultimate tensile strength of a structure obtained from laser sintering of nanoparticles is used as an example to illustrate the proposed UQ framework.